The Factors That Helped To Accept And Refine Some Of The Works Of Ignorance Approved By Islam - Basri, Ibrahim; Mohamed Fathy, Mohamed Abdelgelil (2018)
This study was conducted to determine the actual position of political syar'iyyah from the perspective of Islam and its practices in the context of the state of Kelantan, especially in the field of art and entertainment. The study also followed up with the state government and police of the arts, as well as reforms carried out from 1990 to 2015. The focus of this research focuses on the application of the basic arts and entertainment through the enforcement of the Control of Entertainment and Places of Entertainment 1998, Cultural Performance Guidelines (entertainment) Act 1998 and Control of Entertainment Enactment 2003, which became the main purpose of the exercise of political syar'iyyah. Analysis carried out on the action and reform the state government to the arts by syar'iyyah political perspective. The study employs a library and analysis of official documents such as circulars, news, enactment and guidelines issued by the state government. The study found that ijtihad and reforms undertaken during the period managed to bring about change and give the benefit to the community in Kelantan. It is hoped that this study can contribute to the enrichment of the cultural heritage of the Malay Muslims in accordance with the tenets and formation syar'iyyah political capital of the arts and entertainment that coincide with Islamic law. We hope this study will help art researchers in the future.